1975
DOI: 10.1212/wnl.25.9.845
|View full text |Cite
|
Sign up to set email alerts
|

Nationwide survey of multiple sclerosis in Japan Clinical analysis of 1,084 cases

Abstract: Between October 1972 and October 1973, the first nationwide survey of the multiple sclerosis group of diseases in Japan was performed by the Multiple Sclerosis Research Committee of Japan, supported by the Japan Ministry of Health and Welfare. Reports on 1,084 patients with the multiple sclerosis group were collected: 509 patients with multiple sclerosis, 82 with Devic's disease, 357 with "multiple sclerosis possible," and 136 with "other or unclassified demyelinating diseases." The natural history in the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
88
1
1

Year Published

1981
1981
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(102 citation statements)
references
References 0 publications
12
88
1
1
Order By: Relevance
“…According to its clinical course, MS can be described as relapsing-remitting type (RR-MS), secondary progressive type (SP-MS), in which a progressive phase follows an initial relapsingremitting phase, or primary progressive type (PP-MS), in which the disease shows a progressive course from its onset. On the other hand, concerning the sites of involvement, there have been several reports that Oriental MS patients more commonly show clinical evidence of major involvement of the optic nerves and spinal cord than Caucasian MS patients (1). In addition, we previously reported the clinical and immunogenetic characteristics of two further MS subtypes in Japanese populations, namely opticospinal MS (OS-MS), in which the clinically estimated main lesions are confined to the optic nerves and spinal cord, and conventional MS (C-MS), which shows disseminated lesions in the central nervous system (CNS), including the cerebrum, cerebellum or brainstem (2-4).…”
Section: Introductionmentioning
confidence: 99%
“…According to its clinical course, MS can be described as relapsing-remitting type (RR-MS), secondary progressive type (SP-MS), in which a progressive phase follows an initial relapsingremitting phase, or primary progressive type (PP-MS), in which the disease shows a progressive course from its onset. On the other hand, concerning the sites of involvement, there have been several reports that Oriental MS patients more commonly show clinical evidence of major involvement of the optic nerves and spinal cord than Caucasian MS patients (1). In addition, we previously reported the clinical and immunogenetic characteristics of two further MS subtypes in Japanese populations, namely opticospinal MS (OS-MS), in which the clinically estimated main lesions are confined to the optic nerves and spinal cord, and conventional MS (C-MS), which shows disseminated lesions in the central nervous system (CNS), including the cerebrum, cerebellum or brainstem (2-4).…”
Section: Introductionmentioning
confidence: 99%
“…It is thought that there are fewer cases of multiple sclerosis (MS) in Japan than in Western countries, and previous studies have emphasized some distinct clinical features of Japanese MS (1)(2)(3)(4). Prevalence studies in Western Europe (5), North America (6) and Southern hemisphere (7,8) have shown an increasing frequency of MS with increasing latitude.…”
Section: Introductionmentioning
confidence: 99%
“…From its remitting and exacerbating course, and elevated CSF IgG, the diagnosis of multiple sclerosis was clinically definite, although the patient showed relatively unusual manifestations such as complete quadriplegia, severe visual impairment, epilepsy and deafness. Our former studies,7 8 …”
Section: Discussionmentioning
confidence: 91%